AN ALTERNATIVE AGE MODEL FOR THE PALEOCENE-EOCENE THERMAL MAXIMUM USING EXTRATERRESTRIAL 3HE - Farley K.A.; Eltgroth S.F. (My University, 2003)
A continuous age model for the brief climate excursion at the Paleocene-Eocene boundary has been constructed by assuming a constant flux of extraterrestrial 3He (3HeET) to the seafloor. 3HeET measurements from ODP Site 690 provide quantitative evidence for the rapid onset (<few kyr) and short duration (<120 of global warming the associated disturbance to earth's surficial carbon budget at this time. these observations support astronomically calibrated age models indicating extremely rapid release isotopically light carbon, possibly from seafloor methane hydrate, as proximal cause event. however, 3HeET technique indicates a previously unrecognized and extreme increase in sedimentation rate coincident with the return of climate proxies to pre-event values. The 3HeET-based age model thus suggests a far more rapid recovery from the climatic perturbation than previously proposed or predicted on the basis of the modern carbon cycle, and so may indicate additional or accelerated mechanisms of carbon removal from the ocean-atmosphere system during this period. 3HeET was also measured at ODP Site 1051 to test the validity of the Site 690 chronology. Comparison of these data sets seems to require removal of several tens of kyr of sediment within the climatic excursion at Site 1051, an observation consistent with sediment structures and previous age modeling efforts. The Site 1051 age model shows a ~30 kyr period in which climate proxies return toward pre-event values, after which they remain invariant for ~80 kyr. If this rise represents the recovery interval identified at Site 690, then the 3HeET-based age models of the two sites are in good agreement. However, alternative interpretations are possible, and work on less disrupted sites is required to evaluate the reliability of the proposed new chronology of the climate excursion. Regardless of these details, this work shows that the 3HeET technique can provide useful independent evidence for the development and testing of astronomically calibrated age models.
Keywords: Eocene; Paleocene; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Эоцен; Кайнозой::Палеоген::Палеоцен